Role of seed priming in improving seed germination and seedling growth of maize (Zea mays L.) under rain fed condition - Shrestha, Avinash; Pradhan, Shreena; Shrestha, Jenny; Subedi, Mahesh (Journal of Agriculture and Natural Resources, 2019)
Seed priming enhances early seed emergence and proper crop stand establishment which enables the crop to capture more soil moisture, nutrients, and solar radiation. An on-farm experiment was conducted in Okhaldhunga, Nepal to study the effect of six different priming treatments (50 millimoles common salt solution, 200 millimoles urea solution, 1 percent MOP solution, 2.5 times diluted urine, water, and control) on germination and growth of two maize varieties, Manakamana-3 and Nutan-IL60. The experiment was set up in factorial randomized complete block design with three replications. Various germination traits: germination percent, seedling vigour, germination index, mean germination time, and seedling growth traits: shoot length, root length, and dry root weight, were studied. Nitrogen-based (Urea and Urine) priming resulted the most desirable change for the studied traits. Nitrogen-based priming also had significant positive effect on stress tolerance related traits like root length and dry root weight.